Metabolism of Soyasaponin I by Human Intestinal Microflora and Its Estrogenic and Cytotoxic Effects - Chang, Seo-Young; Han, Myung-Joo; Han, Sang-Jun; Kim, Dong-Hyun (Biomolecules & therapeutics, 2009)
Metabolites of Soyasaponin I, a major constituent of soybean, by human intestinal microflora were investigated by LC-MS/MS analysis. We found four peaks, one parental constituent and three metabolites: m/z 941 [M-H]−, m/z 795 [M-rha-H]−, m/z 441 [aglycone-H2O＋H]＋, and m/z 633 [M-rha-gal-H]−, which was an unknown metabolite, soyasapogenol B 3-β-D-glucuronide. When soyasaponin I was incubated with the human fecal microbial fraction from ten individuals for 48 h, soyasaponin I was metabolized to soyasapogenol B via soyasaponin III and soyasapogenol B 3-β-D-glucuronide or via soyasaponin III alone. Both soyasaponin I and its metabolite soyasapgenol B exhibited estrogenic activity. Soyasaponin I increased the proliferation, mRNA expression of c-fos and pS2, in MCF7 cells more potently than soyasapogenol B. However, soyasapogenol B showed potent cytotoxicity against A549, MCF7, HeLa and HepG2 cells, while soyasaponin I did not. The cytotoxicity of soyasapogenol B may prevent its estrogenic effect from increasing dose-dependently. These findings suggest that orally administered soyasaponin I may be metabolized to soyasapogenol B by intestinal microflora and that soyasapogenol B may express a cytotoxic effect rather than an estrogenic effect. KCI Citation Count: 16